2021
DOI: 10.7759/cureus.18516
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Clinical and Ultrasonographic Hip Screening in Neonates for Developmental Dysplasia of the Hip

Abstract: Developmental dysplasia of the hip (DDH) is a musculoskeletal condition occupying any point along a spectrum of anatomical abnormalities that alter the stability of the newborn hip. Presentation varies throughout infancy and the majority of cases, especially those that are mild in nature, tend to resolve without intervention. An analysis of outcomes was conducted on infants born over a two-year period at a single-center, community hospital in East Toronto. The unwritten norm at the institution has become to or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…As it is transferred to the female infant, it causes changes and effects similar to those of maternal pelvic relaxation in female infant. [5] The prevalence of DDH in this study was 1.4:1, which is consistent with the literature. A study in the United Kingdom showed that DDH was significantly more prevalent among female newborns, with a 7:1 ratio.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As it is transferred to the female infant, it causes changes and effects similar to those of maternal pelvic relaxation in female infant. [5] The prevalence of DDH in this study was 1.4:1, which is consistent with the literature. A study in the United Kingdom showed that DDH was significantly more prevalent among female newborns, with a 7:1 ratio.…”
Section: Discussionsupporting
confidence: 92%
“…This implies that early detection and treatment of DDH would improve outcomes through early intervention and the application of short and less invasive treatments. [5] Various risk factors are believed to be involved in the development of DDH. These included female sex, hip instability, breech delivery, maternal estrogen levels, and family history.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variation in the reported incidence of DDH among different populations leads to the lack of consensus regarding the treatment protocol for this condition. Many authors suggest implemetning a protocol that includes clinical and ultrasonography examinations for DDH in high-risk individuals (5,6,7). Because of the high incidence of DDH in our country, a combined protocol that includes universal mandatory physical examination and ultrasound hip screening up to 8 weeks of age has been accepted.…”
Section: Introductionmentioning
confidence: 99%